Clostridium sticklandii glycine reductase selenoprotein A gene: cloning, sequencing, and expression in Escherichia coli. - Garcia, G E (1992)
Gene grdA, which encodes selenoprotein A of the glycine reductase complex from Clostridium sticklandii, was identified and characterized. This gene encodes a protein of 158 amino acids with a calculated M(r) of 17,142. The known sequence of 15 amino acids around the selenocysteine residue and the known carboxy terminus of the protein are correctly predicted by the nucleotide sequence. An opal termination codon (TGA) corresponding to the location of the single selenocysteine residue in the polypeptide was found in frame at position 130. The C. sticklandii grdA gene was inserted behind the tac promotor of an Escherichia coli expression vector. An E. coli strain transformed with this vector produced an 18-kDa polypeptide that was not detected in extracts of nontransformed cells. Affinity-purified anti-C. sticklandii selenoprotein A immunoglobulin G reacted specifically with this polypeptide, which was indistinguishable from authentic C. sticklandii selenoprotein A by immunological analysis. Addition of the purified expressed protein to glycine reductase protein components B and C reconstituted the active glycine reductase complex. Although synthesis of enzymically active protein A depended on the presence of selenium in the growth medium, formation of immunologically reactive protein did not. Moreover, synthesis of enzymically active protein in a transformed E. coli selD mutant strain indicated that there is a nonspecific mechanism of selenocysteine incorporation. These findings imply that mRNA secondary structures of C. sticklandii grdA are not functional for UGA-directed selenocysteine insertion in the E. coli expression system.